"The world is different from the bridge to here": social representations about favelas of Florianópolis - Martins, João Rodrigo Vedovato; Ferreira, Rafael Rodrigo (Laboratório Editorial Faculdade de Ciências e Letras, 2015)
This essay is intended to develop an analysis of the social representations that the academic community, specifically the student body of the Federal University of Santa Catarina / Florianópolis (UFSC), has on the favelas that are located around the campus, which are: “Morro Pantanal”, “Morro da Carvoeira” and “Serrinha”, and their population.